Pemeliharaan dan Pembiayaan Nafkah Anak Pasca Perceraian (Studi Kasus Putusan Nomor 590/Pdt.G/2019/PN.Bks) - Lestari, Dhona Indah; Hapsari, Hening (Wajah Hukum, 2024)
Child care involves both parents, namely the father and mother, as parties who have responsibility for their children, even though some marriages end in divorce. This research aims to find out and examine how maintenance and financing of maintenance for children after divorce occurs according to statutory regulations. Child care after divorce is regulated in Law Number 35 of 2014 concerning Child Protection and Law Number 1 of 1974 concerning Marriage. The research method used is a normative or doctrinal juridical type, namely research that refers to legal norms contained in statutory regulations and norms that apply in community life. The research results in decision number 590/Pdt.G/2019/PN.Bks show that fulfilling children's maintenance after their parents' divorce has not gone completely well. This is because the ex-husband, after officially divorcing, no longer carries out his obligations. The conclusion in this problem is that child support is still not being met and it is necessary to establish an official institution so that there is supervision over the provision of child support after divorce, whether it has really been carried out in accordance with the governing law.